MitoTracker Deep Red (MTDR) Is a Metabolic Inhibitor for Targeting Mitochondria and Eradicating Cancer Stem Cells (CSCs), With Anti-Tumor and Anti-Metastatic Activity In Vivo - Sargiacomo, Camillo; Stonehouse, Sophie; Moftakhar, Zahra; Sotgia, Federica; Lisanti, Michael P. (Frontiers in Oncology, 2021)
MitoTracker Deep Red (MTDR) is a relatively non-toxic, carbocyanine-based, far-red, fluorescent probe that is routinely used to chemically mark and visualize mitochondria in living cells. Previously, we used MTDR at low nano-molar concentrations to stain and metabolically fractionate breast cancer cells into Mito-high and Mito-low cell sub-populations, by flow-cytometry. Functionally, the Mito-high cell population was specifically enriched in cancer stem cell (CSC) activity, i) showing increased levels of ALDH activity, ii) elevated 3D anchorage-independent growth, iii) larger overall cell size (>12 micromolar) and iv) Paclitaxel-resistance. The Mito-high cell population also showed enhanced tumor-initiating activity, in an in vivo preclinical animal model. Here, we explored the hypothesis that higher nano-molar concentrations of MTDR could also be used to therapeutically target and eradicate CSCs. For this purpose, we employed an ER (+) cell line (MCF7) and two triple negative cell lines (MDA-MB-231 and MDA-MB-468), as model systems. Remarkably, MTDR inhibited 3D mammosphere formation in MCF7 and MDA-MB-468 cells, with an IC-50 between 50 to 100 nM; similar results were obtained in MDA-MB-231 cells. In addition, we now show that MTDR exhibited near complete inhibition of mitochondrial oxygen consumption rates (OCR) and ATP production, in all three breast cancer cell lines tested, at a level of 500 nM. However, basal glycolytic rates in MCF7 and MDA-MB-468 cells remained unaffected at levels of MTDR of up to 1 micromolar. We conclude that MTDR can be used to specifically target and eradicate CSCs, by selectively interfering with mitochondrial metabolism, by employing nano-molar concentrations of this chemical entity. In support of this notion, MTDR significantly inhibited tumor growth and prevented metastasis in vivo, with little or no toxicity observed. Therefore, in the future, MTDR could also be modified and optimized via medicinal chemistry, to further increase its potency and efficacy, for its ultimate clinical use in the metabolic targeting of CSCs for their eradication.